PERENCANAAN DAN PERANCANGAN TERMINAL PELABUHAN PENUMPANG DI DESA KUSAMBA: Bahasa Indonesia - I Putu Egatama Arya Putra; I Wayan Parwata; I Wayan Widanan; Ni Putu Ratih Pradnyaswari Anasta Putri (Undagi : Jurnal Ilmiah Jurusan Arsitektur Universitas Warmadewa, 2025)
This planning is based on an increase in the number of tourists coming to Bali every year, namely 2.2 million tourists in 2022 and increasing by 114 percent in 2023 with a total of 5.3 million tourists. Kusamba village, Dawan subdistrict, Klungkung regency is a strategic area and very close to Nusa Penida and Nusa Lembongan which makes this village a place for sailing boats wishing to cross to the island, therefore most of the Kusamba community depends on the tourism sector. This data shows that there is great potential for business opportunities for the surrounding community. The aim of this research is to plan and design passenger-specific port terminal facilities to solve current problems. Carrying the concept of "Comfortable Harbor and Economic Opportunities” is a concept that provides adequate facilities and also increases economic opportunities for local communities with a traditional atmosphere to enhance the experience of visiting tourists and raises the theme "Neo-Vernacular Architecture" with a response to modernism. combining traditional elements with a modern twist. This theme emphasizes the importance of local culture and the use of local materials as well as harmony between buildings and the environment